Drop Shafts for Narragansett Bay Commission CSO Abatement Program, Providence, Rhode Island - Rafael C. Castro; Geoffrey Hughes; Fredrick (Rick) Vincent; Philip H. Albert (Society for Mining, Metallurgy & Exploration, 2007)
Seven pairs of drop and ventilation shafts, between two and nine feet in diameter, will convey combined sewer flow to a 230-foot-deep, 26-foot diameter storage tunnel. This paper will present case histories for each site. Discussion will include functional requirements, program and site access constraints, structural design, geology, the variety of excavation and lining construction methods used, and lessons learned. Noteworthy observations include the importance of assuring competent ground sup-port at the soil-bedrock interface and of achieving tight verticality tolerance using both top-down and raise bore excavation methods.